Neuroenchancement in normal ageing : preserving cognitive status through pharmacological interventions - Wang, Boon Wan (Trinity College (Dublin, Ireland). School of Psychology, 2012)
The preclinical work presented here seeks to establish an enhancement of memory functions in healthy ageing rats via the manipulation of behavioural tasks. This series of studies compared behavioural deficits between thirteen and three months olds male Wistar rats. The motive of using middle-aged animals was to ascertain if cognitive functions were intact prior to severe ageing and, more importantly, if procognitive therapy was able to prevent consequential damage to memory due to advancing age. The task employed was a Water Plus Maze task which was consisted of two different types of trials (fixed and multiple-start) spanning three separate sessions. The extended paradigm allows further insight into different time-points especially the acute (beginning of trials) and chronic (end of trials) drug effects. We were able to demonstrate that manipulating the central cholinergic system and maintaining glucoregulatory functions can alleviate age-related cognitive deficits.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin.